PEMBUATAN TEKNOLOGI TEPAT GUNA UNTUK PENGOLAHAN SAMPAH ORGANIK MENJADI PUPUK CAIR DESA KENONGOREJO KECAMATAN PILANGKENCENG KABUPATEN MADIUN - Andri Wahyu Utomo; Adika Malik Ramadhan, Ervinda Ika Nur Aysah, Yuni Kartika (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Kenongorejo Village is a village that is used as a place for KKN Group 56. In living in Kenongorejo Village, of course there is a processing center which is the target of the community to grow about environmental cleanliness. Waste processing is one way to keep the environment clean in Kenongorejo Village. Garbage is one of the main views in the cleanliness of the surrounding environment. Waste in processing is divided into two, namely organic waste and non-organic waste. Waste in the work process needs processing which is one of the perfections in recycling. In this waste processing aims to process organic waste into liquid fertilizer. Processing waste by turning it into liquid fertilizer takes a long time, so the process involves the people of Kenongorejo Village. Processing of liquid fertilizer requires materials, namely household food scraps such as leftover vegetables, rotten fruits and vegetable peelings which are household waste so that they can be used to make water fertilizer. From that the process of making liquid fertilizer takes a long time so that people must care about the environment and must create self-awareness in the environment